Method for alkalization or realkalinization of electrode active materials
By electrochemical alkalizing treatment in alkali metal salt solution in electrochemical reactor, the safety and economic problems of using metal lithium in lithium battery manufacturing are solved, and efficient reconstruction and relithization of lithium battery waste electrode materials are achieved. .
Patent Information
- Application Number
- CN202080078863.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-13
- Filing Date
- 2020-11-13
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-11-13
AI Technical Summary
The use of metal lithium as a lithium source in the existing lithium battery manufacturing has safety and fire hazards, and the economic cost is high. It is difficult to reconstruct the electrode material after the lithium battery is discarded, and the relithiation process is complicated and the efficiency is low.
The electrochemical alkalization treatment is carried out in the alkali metal salt solution in the electrochemical reactor, and the electrochemical active material with insufficient alkali metal is alkaline to form a stable alkaline electrochemical active material for preparation of new electrode materials or recycling. use.
The production of electrochemically active materials containing alkali metals is achieved safely and economically, avoiding the risk of using metal lithium, improving the efficiency of electrode material reconstruction of lithium battery waste, and simplifying the relithiation process.
Smart Images

Figure BDA0003640652470000221 
Figure HDA0003640652480000011 
Figure HDA0003640652480000021
Abstract
Description
[0001] Related Applications
[0002] This application claims priority under applicable law to U.S. Provisional Patent Application No. 62 / 934,782, filed on November 13, 2019, the contents of which are incorporated herein by reference in their entirety for all purposes. Technical Field
[0003] The present technology generally relates to the field of methods for intercalating or reintercalating alkali metal ions into electrochemically active materials, such as for producing metal oxides and phosphates containing alkali metals.
[0004] background
[0005] In lithium battery manufacturing, the positive electrode is usually made by coating a suspension of active materials, conductive materials and binders on a current collector, usually aluminum foil, and then drying. The active material is usually a lithiated metal oxide or a lithiated metal phosphate, wherein the metal can be a transition metal or a combination of two or more transition metals. The electrochemical cell is usually assembled with the negative electrode and the separator in a discharged state, that is, the positive electrode is fully lithiated. The exception is the active material V2O5, which is applied to the current collector in a non-lithiated form. In this case, the battery pack is assembled in a fully charged state, which represents a serious safety and fire hazard. The team of Walk et al. has described a method for pre-lithiating a V2O5 electrode under electrochemical conditions using metallic lithium as a negative electrode (see U.S. Patent No. 5,496,663). Such a lithiation method is considered to be electrochemical (galvanic), and requires the use of non-proton and non-aqueous electrolytes due to the presence of metallic lithium as a necessary lithium source and its incompatibility with various solvents, especially aqueous solutions. Another disadvantage of this method is related to the fact that metallic lithium is not the most favorable lithium source from an economic point of view and in view of the precautions required for its use in large-scale processes.
[0006] Liu et al. have also proposed metallic lithium or metallic lithium alloys for relithiation in organic solvents for other electrode materials (see PCT Publication No. WO2019 / 070896A1). However, this method is also based on the use of metallic lithium (or one of its alloys) applied directly to the electrode material and an organic electrolyte solvent in a complex multi-step process involving steps such as forming a soft pack battery, a long wait (usually more than 20 hours), and subsequent removal of excess metallic lithium.
[0007] In order to avoid the above-mentioned disadvantages of using metallic lithium as a lithium source in the lithiation process, others have proposed the use of cheaper materials, such as lithium chloride (instead of metallic lithium) in an organic solvent (see Grant et al., U.S. Patent Application No. US2018 / 0040914). In this method, the electrode material in which lithium is embedded is a lithium-ion battery anode material of the graphite, silicon oxide, and tin oxide type. The lithium halide used in this method produces toxic and corrosive halogen gas at the electrode. Halogen gas can also react with any residual water in the device and produce more corrosive acids, such as HCl or HF, so that additional precautions should be taken during the process of this method.
[0008] Another team proposed the reconstruction of the battery electrode materials depleted of lithium (see Sloop, U.S. Patent No. 9,287,552). Various methods are described, including high temperature solid state reaction, hydrothermal method and reduction conditions in a sealed pressure vessel, which may be carried out in situ by directly introducing the reducing solution into the waste battery. The latter method does not take into account the fact that lithium deficiency is not the only defect in the waste battery. In fact, the electrode may also show the rupture of active materials and binders, lithium inversion, passivation layer, stripping of current collectors, copper reduction deposition on the cathode surface, corrosion of current collectors, etc. In addition, Sloop proposed to separate the positive electrode from the battery intact, which is difficult to implement on a large scale, for example, including taking out the electrode roll ("jelly-roll") from the waste battery, unfolding and sorting the electrode, and processing the entire electrode strip for subsequent steps. This separated electrode will also have the above-mentioned additional defects. Sloop also mentioned but did not show the relithiation of the waste positive electrode, which is deposited in sheets in a charged tray or grid. Poor electrical contact between the electrode sheet and the tray or grid will result in uneven current and potential distribution to promote other electrochemical reactions (such as hydrogen evolution) and lead to low current efficiency and uneven relithiation across the electrode.
[0009] Accordingly, there is a need for new methods for the alkalization or realkalinization of active electrode materials, including methods that can be used to prepare new electrode materials or for their recycling.
[0010] Overview
[0011] According to a first aspect, the present invention relates to a method for electrochemical alkalization of an electrochemically active material, the method comprising the steps of:
[0012] a) obtaining a working electrode comprising a working electrode material on a current collector, the working electrode material comprising an electrochemically active material, optionally a binder and / or an electronically conductive material;
[0013] b) introducing the working electrode in a continuous and / or intermittent mode into an electrochemical reactor having an inert counter electrode and a solution of an alkali metal salt contained in a solvent;
[0014] c) applying a direct current between the working electrode and the counter electrode to obtain an alkalized electrode comprising an alkalized electrochemically active material; and
[0015] d) removing the alkalized electrode obtained in step (c) from the electrochemical reactor;
[0016] The electrochemically active material comprises a metal oxide (including a composite oxide), a metal phosphate, a metal silicate, a metal sulfate or a partially alkalized metal oxide (including a composite oxide), a metal phosphate, a metal silicate or a metal sulfate.
[0017] According to one embodiment, the electrochemically active material is alkali metal deficient. In another embodiment, the method comprises reacting an electrochemically active material of formula I:
[0018] A w-p M n+p x X y O z (I)
[0019] Conversion into an alkalized electrochemically active material of formula II:
[0020] A w M n x X y O z (II)
[0021] in,
[0022] A is an alkali metal;
[0023] M is a transition metal, a post-transition metal or a combination thereof;
[0024] X is selected from P, Si and S;
[0025] O is an oxygen atom;
[0026] w is selected from a value of 1 to 4 and corresponds to the number of A atoms in the alkalized electrochemically active material;
[0027] x is selected from a value of 1 to 5 and corresponds to the number of M atoms;
[0028] y is selected from a value of 0 to 2, wherein when y is 0, X is absent;
[0029] z is selected from values 1 to 12 and corresponds to the number of oxygen atoms in the formula;
[0030] n indicates the oxidation state of M;
[0031] In Formula I, p indicates the average number of missing A atoms and the average increase in the oxidation state of M, where p ≤ w (preferably 0 < p ≤ 1); and
[0032] where w, y, z, n, and p are selected to provide a stable electrically neutral compound.
[0033] In another embodiment, in Formula I, p = w, A is absent, and the electrochemically active material of Formula I is of Formula I(a): M n +p x X y O z . In another embodiment, X is phosphorus, y is 1, and z is 4. In another embodiment, M is Fe, Ni, Mn, Co, or a combination of at least two thereof. In an alternative embodiment, M is V, Mn, Ni, Co, Fe, Cr, Ti, Zr, Sn, or a combination of at least two thereof. In yet another embodiment, y is 0 and X is absent. According to some preferred embodiments, A is Li, Na, or K, or A is Li.
[0034] In another embodiment, the electrochemically active material or the alkalized electrochemically active material is further doped by partial substitution of M with a transition metal (such as V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Mo, W, or Y) and / or a metal of a non-transition metal (such as Mg, Ca, Sr, Al, Sb, or Sn).
[0035] In another embodiment, the solvent is selected from an aqueous solvent, an organic solvent, or a mixture thereof. For example, the solvent is water.
[0036] In other embodiments, the alkali metal salt comprises at least one of an alkali metal sulfate, carbonate, bicarbonate, hydroxide, nitrate, acetate, oxalate, or phosphate. In one embodiment, the alkali metal salt is an alkali metal sulfate. In another embodiment, the alkali metal salt is an alkali metal bicarbonate. For example, where step (b) and / or (c) is carried out in the presence of gaseous carbon dioxide. In another embodiment, the method further comprises the step of adjusting the pH of the solution to a pH suitable for the electrochemically active material of step (a) (for example, for FePO4, adjusting the pH to between 5 and 9, preferably between 6 and 7.5). In one embodiment, the alkali metal of the alkali metal salt is lithium.
[0037] In other embodiments, step (c) is performed in a continuous or batch mode. In another embodiment, step (c) is performed in a continuous mode, wherein the working electrode is introduced into the electrochemical reactor on one side and moves along a specified path so that the working electrode maintains a constant distance from the counter electrode while moving along the electrochemically active area of the electrochemical reactor to maintain a relatively uniform current and potential distribution. In another embodiment, the speed at which the working electrode moves through the electrochemical reactor is adjusted based on the residence time required to achieve the desired alkalization level at the applied current density.
[0038] In yet another embodiment, step (c) is performed in a controlled current density mode between the working electrode and the counter electrode. Alternatively, step (c) is performed in a controlled voltage mode between the working electrode and the counter electrode.
[0039] In other embodiments, the electrochemically active material is FePO4 or partially delithiated LiFePO4, and the current density at the working electrode is in the range of 0.001 A / g to 100 A / g active LiFePO4, preferably in the range of 1 to 15 A / g active LiFePO4.
[0040] In another embodiment, step (c) is performed at a temperature of 5° C. to 90° C., preferably 25° C. to 50° C. In some embodiments, step (b) may further comprise a reference electrode.
[0041] In other embodiments, the above method further comprises a step (e) of washing the alkalized electrochemically active electrode material of the alkalized electrode and / or a step of drying the alkalized electrochemically active electrode material of the alkalized electrode.
[0042] In some further embodiments, the working electrode material comprises a binder selected from fluoropolymer binders and other solvated polymer binders. According to one embodiment, the binder is a fluoropolymer binder such as PVDF, HFP, PVDF-Co-HFP or PTFE. According to another embodiment, the binder is a solvated polymer binder selected from poly(ethylene oxide), poly(propylene oxide), poly(dimethylsiloxane), poly(alkylene carbonate), poly(alkylene sulfone), poly(alkylene sulfonamide), polyurethane, poly(vinyl alcohol) and copolymers (block, random, alternating, statistical, etc.) comprising at least one of the above polymers or monomers thereof, and a combination of at least two of them, wherein the polymer is optionally branched and / or cross-linked.
[0043] In another embodiment, the working electrode material comprises an electronically conductive material selected from carbon black (e.g., Ketjen TM black and Super P TM ), acetylene black (such as Shawinigan black and DenkaTM black), graphite, graphene, carbon fibers or nanofibers (such as vapor grown carbon fibers (VGCFs)), carbon nanotubes (e.g., single-walled or multi-walled), and combinations of at least two thereof.
[0044] In some embodiments, the working electrode material is an electrode material (eg, a positive electrode material) from a spent battery, and step (a) comprises at least one step of separating the electrode material from other elements of the spent battery and applying the material to a current collector.
[0045] In other embodiments, step (a) comprises mixing the electrochemically active material, the binder, and optionally the electronically conductive material in a solvent, applying the mixture to a current collector, and drying.
[0046] According to a second aspect, the present invention relates to an electrode obtained by a method as defined above.
[0047] According to a third aspect, the present invention relates to a method for electrochemical alkalization of an electrochemically active material, the method comprising the steps of:
[0048] (i) adding an electrochemically active material to a solution containing a reducing agent and an alkali metal salt in a solvent to produce an alkalized electrochemically active material;
[0049] (ii) separating the alkalized electrochemically active material from the solution; and
[0050] (iii) electrochemically treating the solution separated in step (ii) to regenerate the reducing agent in the solution.
[0051] In one embodiment, the electrochemically active material and the alkalized electrochemically active material are as defined herein. According to another embodiment, the electrochemically active material is alkali-deficient. In another embodiment, the reducing agent is a reducing member of a redox pair having a lower redox potential than the electrochemically active material to be reduced (alkali-deficient). According to one embodiment, the redox pair comprises a Fe(II) / Fe(III) complex, for example selected from [Fe(CN)6] 3- / [Fe(CN)6] 4- 、[Fe(nta)] / [Fe(nta)] - , [Fe(tdap)] 2- / [Fe(tdap)] 3- , [Fe(edta)] - / [Fe(edta)] 2- , [Fe(citrate)] / [Fe(citrate)] - , [Fe(TEOA)OH] - / [Fe(TEOA)OH]- and [Fe(oxalate)] + / [Fe(oxalate)].
[0052] According to one embodiment, step (i) further comprises a step of deoxygenating the solution. According to another embodiment, steps (i) and / or (iii) are performed in the presence of a gas capable of eliminating the presence of oxygen.
[0053] In another embodiment, the alkali metal salt is selected from alkali metal sulfates, carbonates, bicarbonates, hydroxides, nitrates, acetates, oxalates, phosphates and combinations thereof. In one embodiment, the alkali metal salt is an alkali metal sulfate. In another embodiment, the alkali metal salt is an alkali metal bicarbonate, for example, wherein step (i) is carried out in the presence of gaseous carbon dioxide. In another embodiment, the method further comprises a step of adjusting the pH of the solution to a pH suitable for the electrochemically active material of step (i) (e.g., for FePO4, adjusting the pH to between 5 and 9, preferably between 6 and 7.5). In one embodiment, the alkali metal of the salt is lithium. In another embodiment, the solvent is an aqueous solvent.
[0054] According to one embodiment, the electrochemical treatment step (iii) is carried out in an electrolytic cell by passing an electric current between at least one cathode and at least one anode. In one embodiment, the electrolytic cell comprises at least one ionic or non-ionic diaphragm installed between the anode and the cathode to protect the regenerated reducing agent. In another embodiment, the electrolytic cell further comprises a system for keeping the solution deoxygenated, for example, the system comprises an oxygen-free gas such as carbon dioxide, nitrogen or argon to maintain the electrolytic cell.
[0055] In yet another embodiment, the electrochemically active material is in the form of a suspension in the solution of step (i), and step (ii) is performed by filtration, centrifugation or decantation, optionally followed by a washing step.
[0056] Alternatively, the electrochemically active material is contained in an electrode material on a current collector (forming an electrode), and step (ii) comprises removing the electrode from the solution, optionally followed by a washing step.
[0057] In one embodiment of this alternative, the electrode material further comprises a binder, for example selected from fluoropolymer binders and other solvated polymer binders. According to one embodiment, the binder is a fluoropolymer binder (such as PVDF, HFP, PVDF-Co-HFP or PTFE). Alternatively, the binder is a solvated polymer binder selected from poly(ethylene oxide), poly(propylene oxide), poly(dimethylsiloxane), poly(alkylene carbonate), poly(alkylene sulfone), poly(alkylene sulfonamide), polyurethane, poly(vinyl alcohol) and copolymers (block, random, alternating, statistical, etc.) comprising at least one of the above polymers or monomers thereof, and combinations of at least two thereof, wherein these polymers are optionally branched and / or cross-linked. According to another embodiment, the electrode material further comprises an electronically conductive material, for example selected from carbon black (such as Ketjen TM black and Super P TM ), acetylene black (such as Shawinigan black and Denka TM black), graphite, graphene, carbon fibers or nanofibers (such as vapor grown carbon fibers (VGCFs)), carbon nanotubes (e.g., single-walled or multi-walled), and combinations of at least two thereof.
[0058] In another embodiment, the method further comprises drying the alkalized electrochemically active material.
[0059] According to a fourth aspect, the present invention relates to an electrode comprising an alkalized electrochemically active material obtained by a process as defined herein, a binder and optionally an electronically conductive material.
[0060] According to a fifth aspect, the present invention relates to an electrochemical cell comprising a negative electrode, a positive electrode and an electrolyte, wherein the positive electrode is an electrode as defined herein; or a battery comprising at least one such electrochemical cell. For example, the battery is a lithium battery or a lithium ion battery.
[0061] In another embodiment, the electrochemical cell or battery as defined herein is used in a mobile device, such as a mobile phone, camera, tablet or laptop, in an electric or hybrid vehicle, or in renewable energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 A graph showing lithium leaching rate versus time during delithiation according to Example 1(a) is presented.
[0064] Figure 2 X-ray diffraction patterns of pristine LiFePO4 (top line) and its delithiated FePO4 (bottom line) according to Example 1(a) are shown.
[0065] Figure 3 Linear sweep voltammetry of a FePO4 electrode performed as described in Example 1(c) from 0 V vs. OCP (open circuit potential) to -1 V vs. SCE (saturated calomel electrode) at a rate of 1 mV / s is presented.
[0066] Figure 4 X-ray diffraction patterns of pristine LiFePO4 (top), delithiated FePO4 (middle), and relithiated LiFePO4 (bottom) according to Example 1 are shown.
[0067] Figure 5 The voltammogram of the galvanostatic relithiation of a FePO4 electrode carried out at 10 mA according to Example 2 is shown.
[0068] Figure 6 X-ray diffraction patterns of pristine LiFePO 4 (top), delithiated FePO 4 (middle), and relithiated LiFePO 4 (bottom) according to Example 2 are presented.
[0069] Figure 7 The galvanic response of two FePO4 electrodes subjected to potentiostatic relithiation at -0.2 V vs. SCE at 25°C (dashed line) and 50°C (solid line) according to Example 3 is presented.
[0070] Figure 8 X-ray diffraction patterns of pristine LiFePO4 (top), relithiation of LiFePO4 at 25°C (middle), and relithiation of LiFePO4 at 50°C (bottom) according to Example 3 are presented.
[0071] Fig. 9 Cathodic linear sweep voltammetry of a FePO 4 electrode performed in 0.5 M aqueous LiHCO 3 solution between 0 V vs. OCP to -1.1 V vs. SCE at a flow rate of 1 mV / s according to Example 4 is presented.
[0072] Fig.10 The galvanic response of two FePO 4 electrodes subjected to potentiostatic relithiation at −0.2 V vs. SCE at 25° C. according to Example 4 in 0.25 M Li 2 SO 4 (dashed line) and 0.5 M LiHCO 3 (solid line) are presented.
[0073] Fig.11 X-ray diffraction patterns of pristine LiFePO 4 (top), delithiated FePO 4 (middle), and relithiated LiFePO 4 (bottom) according to Example 4 are presented.
[0074] Fig.12The current change vs. time of the electrode material applied to the aluminum current collector according to the method of Example 5 is shown.
[0075] Fig.13 X-ray diffraction patterns of pristine LiFePO 4 (top), delithiated FePO 4 (middle), and relithiated LiFePO 4 (bottom) electrode materials according to Example 5 are presented.
[0076] Fig.14 The discharge capacity of the relithiated LiFePO4 (circles) according to Example 5 is shown compared to the reference LiFePO4 (triangles).
[0077] Fig.15 The results show that the 2.05V to 4.25V vs. Li at a scan rate of 200mV / sec according to Example 6(b) + Voltammogram of Fe(III)-EDTA solution between 2.5 and 1.5 W.
[0078] Fig.16 Polarization curves according to Example 6(b) are presented in the case of an EDTA-LiOH solution (dashed line) and a Fe(III)-EDTA in LiOH solution (solid line).
[0079] Fig.17 The change in the redox potential of the suspension during the reduction of FePO4 by Fe(II)-EDTA according to Example 7(a) is shown.
[0080] Fig.18 X-ray diffraction patterns of pristine LiFePO 4 (top), delithiated LiFePO 4 (middle), and relithiated LiFePO 4 (bottom) according to Example 7(a) are presented.
[0081] Fig.19 The change in the redox potential of the suspension during the reduction of FePO4 by Fe(II)-citrate according to Example 7(b) is shown.
[0082] Fig. 20 X-ray diffraction patterns of pristine LiFePO 4 (top), delithiated LiFePO 4 (middle), and relithiated LiFePO 4 (bottom) according to Example 7(b) are presented.
[0083] Fig.21 Presented are changes in the Fe(II)-EDTA concentration and redox potential of the solution during the electrolysis process given in Example 8(a).
[0084] Fig. 22The change in the redox potential of the suspension during the reduction of FePO4 by Fe(II)-EDTA generated by the electrolysis of Fe(II)-EDTA according to Example 8(b) is shown.
[0085] Fig.23 X-ray diffraction patterns of pristine LiFePO4 (top), delithiated LiFePO4 (middle), and relithiated LiFePO4 (bottom) according to Example 8(b) are shown.
[0086] Details
[0087] The following detailed description and examples are intended to be illustrative and should not be construed to further limit the scope of the present invention.
[0088] All technical and scientific terms and expressions used herein have the same definitions as commonly understood by those skilled in the art. Nevertheless, for clarity, definitions of some terms and expressions used herein are provided below.
[0089] When the term "about" is used in this article, it means approximately, around, and in the vicinity. When the term "about" is used in relation to a value, it can modify the value, such as by 10% above and below its nominal value. This term can also take into account the probability of random errors in experimental measurements or the rounding of values.
[0090] As used herein, the term "alkalization" refers to the reduction of an active material comprising a metal, accompanied by the insertion of alkali metal ions into the active material. When the alkali metal ions are lithium ions, the term "lithiation" is used. Similarly, the terms "alkalized" and "lithiated" generally refer to materials resulting from alkalization or lithiation, respectively. Similarly, the terms "re-alkalization" and "re-lithiation" refer to the alkalization or lithiation of an active material from which alkali metal ions or lithium ions have been lost or deficient, respectively.
[0091] The present invention therefore relates to the alkalization of an electrochemically active material containing at least one metal in a non-zero oxidation state. The first step in this method is to obtain a working electrode comprising an electrode material on a current collector. The electrode material comprises the electrochemically active material to be alkalized and may comprise other components. For example, the electrochemically active material is uniformly dispersed in a binder and an optional conductive material.
[0092] Electrochemically active materials can generally be defined as comprising metal oxides (including composite oxides), metal phosphates, metal silicates, metal sulfates, or partially alkalized oxides, phosphates, silicates or sulfates thereof. For example, the electrochemically active material is of formula I:
[0093] A w-p M n+p x X y Oz (I)
[0094] Wherein,
[0095] A is an alkali metal (such as Li, Na, and K, preferably lithium);
[0096] M is a transition metal, a post-transition metal, or a combination thereof;
[0097] X is selected from P, Si, and S; and
[0098] O represents oxygen;
[0099] w is selected from the values 1 to 4 and corresponds to the number of A atoms in the alkalized electrochemically active material;
[0100] x is selected from the values 1 to 5 and corresponds to the number of M atoms;
[0101] y is selected from the values 0 to 2, where when y is 0, X is absent;
[0102] z is selected from the values 1 to 12 and corresponds to the number of oxygen atoms in the formula;
[0103] n indicates the oxidation state of M;
[0104] p indicates the average number of missing A atoms and the average increase in the oxidation state of M, where p ≤ w (preferably 0 < p ≤ 1); and
[0105] where w, y, z, n, and p are selected to provide a stable electrically neutral compound.
[0106] The alkalized electrochemically active material obtained by this method has the formula II:
[0107] A w M n x X y O z (II)
[0108] where A, M, X, O, n, w, x, y, and z are as defined herein.
[0109] Examples of the electrochemically active material include compounds of formula I, where p = w, A is absent, and the electrochemically active material of formula I is of formula I(a): M n+p x X y O z . In some examples, X is phosphorus, y is 1, and z is 4.
[0110] Examples of transition metals M include Fe, Ni, Mn, Co or combinations thereof, preferably when X is phosphorus, y is 1 and z is 4. According to another example, the electrochemically active material is FePO4 or partially delithiated LiFePO4. Examples of M may also include metals selected from V, Mn, Ni, Co, Fe, Cr, Ti, Zr, Sn or a combination of at least two thereof. In some examples, y is 0 and X is absent, and Formula I represents an oxide or a composite oxide.
[0111] The electrochemically active material and / or alkalized electrochemically active material may also be doped by partial substitution (10 mol % or less, or 5 mol % or less) of M, for example, by a transition metal (e.g., Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Mo, W, or Y) and / or a non-transition metal (e.g., Mg, Ca, Sr, Al, Sb, or Sn).
[0112] In the first process step, the alkali-deficient material, such as the material of formula I or I(a), can be mixed with all the ingredients required to prepare the electrode of the energy storage device and applied to the current collector. The material to be alkalized can be of commercial origin and included in the working electrode material of the present method to achieve alkalization before use as an electrode in an electrochemical cell. Alternatively, the electrochemically active material to be alkalized can come from a battery recycling process.
[0113] The electrochemically active material may be in the form of microparticles or nanoparticles and / or may further comprise a carbon coating.
[0114] The composition of the electrode material may further comprise at least one binder, such as a polymer binder, preferably a polar and solvating polymer binder.
[0115] The non-limiting examples of the solvated polymer suitable for use as positive electrode binder include polymer binders containing fluorine atoms, such as PVDF, HFP, PVDF-Co-HFP and PTFE. Other examples of solvated polymer binders include poly (ethylene oxide), poly (propylene oxide), poly (dimethylsiloxane), poly (alkylene carbonate), poly (alkylene sulfone), poly (alkylene sulfonamide), polyurethane, poly (vinyl alcohol) and copolymers (block, random, alternating, statistical, etc.) comprising at least one of the above-mentioned polymers or its monomers, and a combination of at least two thereof. These solvated polymers can also be branched and / or crosslinked. Other examples of binders include water-soluble binders, such as SBR (styrene butadiene rubber), NBR (acrylonitrile butadiene rubber), HNBR (hydrogenated NBR), CHR (epichlorohydrin rubber), ACM (acrylate rubber), etc., and cellulose-based binders (such as carboxyalkyl cellulose, hydroxyalkyl cellulose and combinations thereof), or any combination of at least two thereof. It is to be understood that when the solvent used in the present process is an aqueous solvent, a water-soluble binder cannot be used in the present alkalization process.
[0116] Examples of electronically conductive materials include, but are not limited to, carbon black (e.g., Ketjen TM black and Super P TM ), acetylene black (such as Shawinigan black and Denka TM black), graphite, graphene, carbon fibers or nanofibers (such as vapor grown carbon fibers (VGCF)), carbon nanotubes (e.g., single-walled or multi-walled), and combinations of at least two thereof.
[0117] The second step of the method comprises introducing the working electrode into an electrochemical reactor having an inert counter electrode and a solution of an alkali metal salt contained in a solvent. The electrochemical reactor may further include a reference electrode (such as a saturated calomel electrode (SCE)). In another example, the electrochemical reactor may also be equipped with a potentiostat or rectifier for electrolysis. The electrochemical reactor is configured for continuous or batch mode electrolysis and may include additional components, such as an agitation mode and / or a temperature control device for increasing mass transfer to the working electrode.
[0118] The solution contained in the electrochemical reactor acts as an electrolyte and contains at least one alkali metal salt to be embedded in the active material, such as lithium, sodium or potassium salt, preferably lithium salt, preferably excluding halide salt. Examples of suitable salts include sulfates, carbonates, bicarbonates, hydroxides, nitrates, acetates, oxalates or phosphates of alkali metals, such as A2SO4 or AHCO3, wherein A is as defined above. The solvent of the solution is an organic solvent, an aqueous solvent or a combination thereof, preferably an aqueous solvent. For example, the solvent is water (such as distilled water or high purity water). A pH adjustment step may also be included in the method. The pH of the solution must be suitable for the electrochemically active material (and its alkalized form), for example to maintain its stability and avoid its dissolution. For example, when the electrochemically active material to be treated is or its partially alkalized form, the pH is adjusted to between 5 and 9, preferably between 6 and 7.5. For example, if the solution is too acidic, the pH can be adjusted by an alkali hydroxide. A supporting electrolyte may be further added to reduce the resistance of the electrolyte.
[0119] The counter electrode is made of a material that is inert under the electrolysis conditions, such as platinum, noble metal oxides, lead oxide, and may optionally include a catalytic compound layer to reduce the electrode overpotential. For example, in the case of aqueous solutions, the reaction at the counter electrode may result in the release of oxygen, and a dimensionally stable anode may be used as the counter electrode material.
[0120] The third step comprises applying a direct current between the working electrode containing the electrochemically active material with insufficient alkali metal and the counter electrode to obtain an alkalized electrode containing an alkalized electrochemically active material (e.g., as defined in Formula II). This step can be carried out at a temperature of 5°C to 90°C, preferably 25°C to 50°C.
[0121] As mentioned above, the electrochemical reactor can be operated in a continuous or batch mode. In the continuous mode, the working electrode enters the electrochemical reactor from one side and follows a specified path so that the working electrode maintains a constant distance from the counter electrode while moving through the electrochemically active area of the electrochemical reactor to maintain a relatively uniform current and potential distribution. The speed at which the working electrode moves through the electrochemical reactor depends on the residence time required for the desired alkalization level and the current density applied. The electrochemical reactor can be operated in a controlled current density mode or a controlled voltage mode between the working electrode and the counter electrode.
[0122] According to a specific example, the electrochemically active material is FePO4 or partially delithiated LiFePO4, and the current density at the working electrode is in the range of 0.001 A / g to 100 A / g active LiFePO4, preferably in the range of 1 to 15 A / g active LiFePO4.
[0123] Once the target alkalization level is reached, the working electrode is removed from the electrochemical reactor.The thus alkalized electrode is then preferably subjected to a washing step to remove excess electrolyte from the alkalized electrode material, followed by a drying step to remove excess washing fluid.
[0124] When present, a reference electrode may be placed in the reactor to monitor the potential of the working electrode. Its presence will minimize parasitic reactions at the working electrode and maximize the efficiency of the alkalization current.
[0125] In an alternative, a chemical reduction method may also be used for the alkalization of the electrochemically active material as defined herein. This alternative alkalization method comprises a reducing agent and further comprises the step of electrochemically regenerating the reducing agent. For example, the electrochemically active material may be treated with a solution of a reducing agent and an alkali metal salt in a solvent. When the reducing agent and / or the electrochemically active material are easily oxidized in the presence of oxygen, the solution may be deoxygenated before the reducing agent and / or the electrochemically active material is added. Similarly, this step may also be carried out in the presence of a gas (such as CO2, N2 or Ar) that can eliminate the presence of oxygen. The resulting electrochemically active material and the alkalized electrochemically active material are as defined above. Preferably, the electrochemically active material is alkali metal deficient.
[0126] Non-limiting examples of alkali metal salts used in the chemical reduction step include alkali metal sulfates, carbonates, bicarbonates, hydroxides, nitrates, acetates, oxalates and phosphates or any combination thereof. The solvent used is preferably an aqueous solvent.
[0127] In this method, the material to be alkalized can be treated as a suspension in a reactor, separated from the waste reducing agent solution, rinsed and dried, and then used as an active electrode material in electrode manufacturing. The separation of the alkalized material from the waste reducing agent solution can be achieved by typical physical separation methods, such as by filtration, centrifugation or decantation. The separated and dried alkalized material can then be mixed with the components required for preparing the electrode and applied to the current collector. For example, these components may include a binder as defined above and an optional electronic conductive material.
[0128] On the other hand, the material to be alkalized using this method can first be mixed with the components of the electrode material defined above, and then applied to a suitable current collector to obtain an electrode, such as the working electrode described in the above method. The prepared electrode is then treated with a reducing agent solution, for example by immersion in it, washed and dried.
[0129] In both cases, the spent reducing agent is recovered and then regenerated in a subsequent step. For example, the solution containing the spent reducing agent is transferred to a high efficiency, high current density electrochemical (or electrolytic) cell to reduce (and thus regenerate) the spent reducing agent so that it can then be reused to treat the alkali metal-deficient material. For example, the reducing agent regeneration step is performed by an electrochemical process in which an electric current is passed between at least one cathode and at least one anode in an electrolytic cell. Such an electrolytic cell may further comprise at least one ionic or non-ionic membrane mounted between the anode and the cathode to protect the regenerated reducing agent.
[0130] When the regenerated reagent is easily oxidized in the presence of oxygen, the electrolytic cell may further comprise a system for keeping the solution deoxygenated, for example comprising a gas such as carbon dioxide, nitrogen or argon to maintain the electrolytic cell free of oxygen.
[0131] The current density of the electrolytic cell can be increased by influencing the mass transfer in the cell by known methods such as using turbulence promoters, increasing the temperature, etc. and by increasing the effective surface area of the cathode, for example by using materials in the form of felt, grids, etc. In the case where the solvent of the electrolytic solution is water-based, the cathode material is preferably selected from those with high hydrogen overpotential, such as graphite, lead, etc.
[0132] Since the reducing agent can be reused almost indefinitely, it is possible to consider using only electrons as reducing agent for the electrode material, which can be regarded as indirect electrochemical reduction. This method therefore has several advantages (economic, environmental, etc.) compared to the use of non-regenerated reducing agents.
[0133] Various redox pairs can be used as regenerable reductants. The redox pair is selected to have a redox potential lower than the electrochemically active (alkali-deficient) material to be reduced. For example, in the case of FePO4 relithiation, the redox pair should have a redox potential lower than 3.45 V vs. Li / Li+ The redox potential of (see AK Padhi et al., J. Electrochem. Soc., 1997, 144, 1188-1194).
[0134] Another desirable feature of a redox couple is a relatively high solubility, especially in its oxidized form, to avoid the formation of precipitates in the presence of the processed electrode material. Examples of useful redox couples include Fe(II) / Fe(III) complexes, which exhibit interesting properties for use in this indirect electrochemical process. These complexes include, for example, [Fe(CN)6] 3- / [Fe(CN)6] 4- 、[Fe(nta)] / [Fe(nta)] - , [Fe(tdpa)] 2- / [Fe(tdpa)] 3- , [Fe(edta)] - / [Fe(edta)] 2- , [Fe(citrate)] / [Fe(citrate)] - , [Fe(TEOA)OH] - / [Fe(TEOA)OH] - and [Fe(oxalate)] + / [Fe(oxalate)]. These redox pairs are of particular interest for the alkalization of electrochemically active (alkali-deficient) materials containing iron, such as FePO4.
[0135] The advantage of this indirect electrochemical process compared to the direct electrochemical reduction of the electrode material is that it is possible to use much higher current densities and thus increase the productivity of the electrochemical reactor.
[0136] The electrodes produced by the method defined above can then be used directly for preparing electrochemical cells, for example by stacking the electrode with an active counter electrode, the two electrodes being separated by an electrolyte, such as a liquid or gel electrolyte impregnated with a separator, or a solid polymer electrolyte. These electrochemical cells can further be used for preparing electrochemical energy storage devices.
[0137] As indicated above, the material to be alkalized by the present method may be spent electrode material obtained in a battery recycling process, or raw electrode material (or a precursor thereof) to be converted into discharged electrode material before its assembly in an electrochemical cell.
[0138] The present specification also contemplates a battery comprising at least one electrochemical cell as defined herein. For example, the battery is a lithium or lithium ion battery. The present battery and electrochemical cell may be used, for example, in mobile devices such as mobile phones, cameras, tablets or laptops, in electric vehicles or hybrid vehicles, or in renewable energy storage. Example
[0139] The following non-limiting examples are exemplary embodiments and should not be construed as further limiting the scope of the present invention.These examples are better understood with reference to the accompanying drawings.
[0140] Embodiment 1:
[0141] (a) Preparation of delithiated FePO4
[0142] Unused cathode material containing mainly LiFePO4 and a small amount of PVDF and graphite is used to make a delithiation material from a LiFePO4 sample using the method described in patent application US2019 / 0207275 (Amouzegar et al.). 10 parts of this material are dispersed in 100 parts of an aqueous solution containing H2O2 (the amount of H2O2 is adjusted so that the Fe:H2O2 molar ratio is 2:1.33) in a stirred reactor bubbling CO2 gas at a pressure of 30 psi and at room temperature. Filtered samples of the suspension taken out at different time intervals are analyzed by ICP to measure the concentrations of Li, Fe and P. The solid residue from the leaching is then separated by centrifugation, washed with deionized water, and dried in a furnace at 120°C for 48 hours.
[0143] Seven batches were prepared in this way and then combined with one another. Figure 1 The leaching rates of Li, Fe and P obtained for each batch are shown. These results were then used to calculate the leaching efficiency of each element. It was observed that after 30 minutes, close to 80% of Li could be found in solution, and after 75 minutes this parameter reached a value of about 90%. The leaching rates of Fe and P did not exceed 0.5% and 3%, respectively, which indicates a very high selectivity and efficiency of lithium extraction.
[0144] Using the MiniFlex 600 with a cobalt source TM The X-ray diffraction spectra of the solid composite material sample and the original LiFePO4 sample were obtained by the instrument and presented in Figure 2 As can be seen, the sample consists mainly of FePO4 with some residual LiFePO4. In fact, the X-ray diffraction results confirm that the delithiation rate is higher than the delithiation rate calculated from the ICP analysis results (90% for ICP analysis compared to 95% from the diffraction results).
[0145] (b) Preparation of FePO4 electrode
[0146] In order to characterize the electrochemical behavior of the delithiated material of 1(a) during the relithiation process, FePO4 powder was mixed with conductive carbon (Denka TM black and VGCF TM -H, 1:1 weight ratio) and binder (PVDF) were mixed in a weight ratio of 87.5:7.5:5, and then dispersed in N-methyl-2-pyrrolidone (NMP) to form a suspension. Finally, this suspension was coated on a 4.16 cm 2 The final loading of the electrode was about 4.3 mg / cm2 for FePO4. 2 ).
[0147] (c) Relithiation of FePO4 electrode materials
[0148] The electrode prepared in (b) was tested as a working electrode in a three-electrode electrochemical apparatus. A platinum mesh was used as a counter electrode, while a saturated calomel electrode (SCE) served as a reference electrode. The electrolyte consisted of an aqueous Li2SO4 solution (0.25 M), to which LiOH was added to adjust the pH to 7. The temperature was set at 25°C using a double-walled glass electrochemical cell (thermostat). Figure 3 The current vs. potential voltammetry curves at a potential scan rate of 1 mV / s are shown.
[0149] The working electrode was firstly TM 4 instrument (Princeton Applied Research) was scanned from its open circuit potential (in this case 165mV vs. SCE) to -1.0V vs. SCE. It can be seen that except for the reduction peak corresponding to the lithiation of FePO4 to LiFePO4, no other reactions occur in this potential region. This means that operating the cell in this potential window can provide good Coulombic current efficiency for the relithiation process. Figure 4 As shown in , the X-ray diffraction pattern of the relithiated sample is compared with the X-ray diffraction pattern of the original LiFePO4 material and the X-ray diffraction pattern of the delithiated composite material sample, which clearly confirms that after relithiation, the structure of the delithiated sample is restored to that of the original material.
[0150] Embodiment 2:
[0151] To perform electrochemical relithiation under conditions more suitable for large-scale industrial operation, the same type of electrode prepared in Example 1(b) was relithiated under constant current conditions by applying a constant current of 10 mA between the cathode (FePO4 electrode) and the anode (inert electrode, in this case a Pt mesh). The cathode potential was measured relative to a SCE reference electrode to determine the time required to relithiate substantially all of the delithiated FePO4. The electrolysis was carried out in the same type of solution as in Example 1(c) and at the same temperature (25°C).
[0152] The change of cathode potential vs electrolysis time is shown in Figure 5 The initial cathode potential is about 0 V vs. SCE, and as the degree of lithiation of the cathode material increases, it gradually moves to a larger cathode potential over time. After about 1200 seconds, the electrode potential stabilizes and remains constant at -1.4 V vs. SCE, indicating the start of new electrochemical reactions, which include hydrogen evolution.
[0153] Figure 6 X-ray diffraction analysis of the electrode shown in confirms the extremely high degree of reconstruction of FePO4 in lithium ions, so that the conversion rate to LiFePO4 phase is close to 100%. Indeed, the FePO4 peak is clearly transformed into the LiFePO4 peak. Other phases present in the diffraction pattern include stainless steel supports (2θ: 51, 54 and 90) and conductive graphite (2θ: 30).
[0154] The Coulombic efficiency of relithiation was calculated to be greater than 80%, thus confirming the predicted electrochemical behavior shown in Example 1, i.e., under specific conditions of current density at the cathode, it is possible to minimize side reactions (such as hydrogen evolution) to achieve high current efficiency.
[0155] Embodiment 3:
[0156] To evaluate the effect of temperature on the lithiation process, the two electrodes prepared in Example 1(b) were relithiated at 25°C and 50°C in an aqueous Li2SO4 solution (0.5 M) to which LiOH was added to adjust the pH to 7. The relithiation was performed at a constant potential of -0.2 V vs. SCE.
[0157] The change in current between the cathode and anode vs. time is shown in Figure 7 The higher electrochemical relithiation rate at higher temperature (50°C) results in a less pronounced current drop at the beginning of the process and a shorter time to reach nearly zero current between the cathode and anode (the point of almost complete relithiation) compared to relithiation performed at 25°C.
[0158] Figure 8The X-ray diffraction patterns in confirm that both electrodes are highly relithiated, with residual FePO4 being less than 8% and undetectable in the tests at 25°C and 50°C, respectively.
[0159] Embodiment 4:
[0160] To demonstrate the feasibility of directly using LiHCO3 solutions produced during the processing of electrode materials from spent batteries as described in published patent application US2019 / 0207275 (Amouzegar et al.), electrodes similar to those described in Example 1(b) were relithiated in an electrochemical cell using a 0.5M LiHCO3 aqueous solution (made by bubbling CO2 through a suspension of Li2CO3 in water at 30 psi and room temperature). The cell was kept under CO2 by gently bubbling CO2 gas through the electrolyte at pH 7 and 25°C.
[0161] Cathodic linear sweep voltammetry of the electrode at a rate of 1 mV / s between 0 V vs. OCP (open circuit potential) and -1.1 V vs. SCE showed Fig. 9 The same type of relithiation reduction peaks as those observed using Li2SO4 solution in Example 1 were observed, thus indicating the possibility of using LiHCO3 solution as a Li ion source during the relithiation process. Fig.10 As shown in , relithiation in bicarbonate-based electrolytes appears to exhibit better kinetics than sulfate-based electrolytes under similar conditions. Compositional analysis by X-ray diffraction also showed complete relithiation of the electrode (see Fig.11 ).
[0162] Embodiment 5:
[0163] (a) Preparation of FePO4 electrode
[0164] To show that the same method is easily applicable to industrial current collectors used in commercial batteries, the same electrode prepared in Example 1(b) was prepared using a 15 μm thick aluminum current collector coated with a thin carbon layer. TM black and VGCF TM -H, 1:1 weight ratio) and PVDF binder were mixed in a weight ratio of 89:6:5 and dispersed in N-methyl-2-pyrrolidone (NMP). The suspension thus obtained was coated on an aluminum current collector and dried in a furnace. The electrode loading was determined to be approximately 7.12 mg FePO4 / cm 2 .
[0165] (b) Relithiation of FePO4 electrode materials
[0166] To simulate an electrochemical device operating in batch mode, the surface area of the prepared sample (a) was 37.5 cm 2 The electrode strips were installed in an electrochemical cell (using a SS support to maintain a constant distance from the counter electrode) in which a 90 cm 2 Platinum mesh and SCE electrode were used as counter electrode and reference electrode, respectively. The electrolyte was made of Li2SO4 (0.5 M) and the pH was adjusted to 9 using diluted LiOH. The cathode potential was controlled at -200 mV vs. SCE using a potentiostat from Princeton Applied Research. The electrolysis was carried out under stirring and at a temperature of 25°C. Fig.12 The current change vs. time is shown. Once the current has dropped by 95% (in this case after 2860 seconds), the electrolysis is stopped and the working electrode is washed with deionized water and dried.
[0167] X-ray diffraction patterns obtained from pristine LiFePO4, delithiated FePO4, and relithiated LiFePO4 ( Fig.13 ) confirmed that the relithiation process had taken effect. Indeed, the relithiated electrode consisted of 93% LiFePO4 and 7% FePO4. The relithiated LiFePO4 exhibited an orthorhombic structure similar to that of the original LiFePO4.
[0168] (c) Use of relithiated LiFePO4 electrodes in button cells
[0169] The electrochemical properties of the electrode relithiated in (b) and commercial LiFePO4 material applied in the same manner on an aluminum current collector were tested in button cells against metallic lithium. The active material loading calculated as mg LiFePO4 per unit area was 7.32 mg LiFePO4 / cm for the relithiated and pristine LiFePO4 samples, respectively. 2 and 5.88 mg LiFePO4 / cm 2 Both cells were cycled in duplicate between 2 V and 3.8 V at a discharge rate of 1 C and a charge rate of C / 4. A pre-charge / discharge cycle at C / 24 was applied to each coin cell before the cycling procedure. In addition, the cycling procedure involved an initial discharge at C / 12, which was repeated every 20 cycles to monitor the health of the battery pack.
[0170] Fig.14The discharge capacity curves of these electrode materials are shown. It can be seen that both electrode materials show excellent stability in capacity (less than 2% loss after 100 cycles). After 100 cycles, the electrochemically relithiated LiFePO4 material and the reference LiFePO4 material show good and very similar discharge capacities of 138 and 143 mAh / g, respectively, at a discharge rate of 1C. The very small capacity differences may be related to slight differences in the active material loading, i.e., a slightly higher loading of the electrochemically relithiated material may result in a slightly lower capacity.
[0171] Embodiment 6:
[0172] (a) Preparation of Fe(II) / Fe(III) redox couple solution
[0173] i. Preparation of Fe(II) and Fe(III) citrate solutions
[0174] A citric acid solution was prepared by dissolving 3.18 parts of the acid in 200 parts of water. The solution was then basified using a 4M LiOH solution to pH 6. The lithium concentration was adjusted to a minimum of 0.5 M by adding the necessary amount of Li2SO4 and then the volume was adjusted to 250 parts.
[0175] Then, to prepare a ferrous solution, 0.56 parts of hydrated ferrous sulfate (FeSO4.7H2O) was dissolved in 100 parts of the previously prepared citric acid solution.
[0176] Similarly, for the iron solution, 0.21 parts of hydrated iron sulfate (Fe2(SO4)3·xH2O) was dissolved in 100 parts of the citric acid solution prepared above.
[0177] Each solution was filtered at 0.22 μm and then deoxygenated by injection of argon before their subsequent use. If necessary, the pH of each solution was adjusted to a value between 4.5 and 8 using LiOH or H2SO4.
[0178] ii. Preparation of Fe(II) and Fe(III) EDTA solutions
[0179] An EDTA solution was prepared by dissolving 14.6 parts of the salt in its acid form in 100 parts of 1 M LiOH solution. The solution was then basified using 4 M LiOH to pH 6. The lithium concentration was adjusted to a minimum of 0.5 M by adding the necessary amount of Li2SO4 and then the volume was adjusted to 250 parts.
[0180] Then, to prepare the ferrous solution, 2.78 parts of hydrated ferrous sulfate (FeSO4.7H2O) were dissolved in 100 parts of the previously prepared EDTA solution.
[0181] Similarly, for the iron solution, dissolve 1 part hydrated ferric sulfate (Fe2(SO4)3·xH2O) in 100 parts of the previously prepared EDTA solution.
[0182] Each solution was filtered at 0.22 μm and then deoxygenated by injection of argon before their subsequent use. If necessary, the pH of each solution was adjusted to a value between 4.5 and 8 using LiOH or H2SO4.
[0183] (b) Study on the electrochemical properties of the Fe(II) / Fe(III) redox couple
[0184] To confirm the feasibility of reducing FePO 4 to LiFePO 4 by each redox couple prepared in subsection (a) of this example, the electrochemical behavior of Fe(III) solutions of each iron complex was studied in a three-electrode electrochemical device.
[0185] Each Fe(III) solution was placed in the cathode compartment of the cell (under argon blanket), in which a glassy carbon disk (3 mm diameter) was installed as the working electrode. A Pt mesh was placed in the electrolyte-filled anode compartment separated by a sintered carbon disk. An Ag / AgCl electrode was used as the reference electrode.
[0186] Using Versastat TM The voltammograms were obtained using a potentiostat (Princeton Applied Research). Fig.15 Shown at pH 4.5 at a scan rate of 200 mV / sec from 2.05 V to 4.25 V vs. Li + / Li 0 The voltammogram of Fe(III)-EDTA solution was performed between 2 and 3 hours. A large gap (about 650 mV) can be observed between the oxidation peak of Fe(II)-EDTA and the reduction of Fe(III)-EDTA, which is an indication of relatively slow kinetics. However, it can be seen that the oxidation of Fe(II)-EDTA is at about 3.16 V vs. Li + / Li, which is significantly higher than the 3.45V vs.Li required for the reduction of FePO4 to LiFePO4. + / Li has a more negative minimum potential.
[0187] Table 1 shows the potential value at which oxidation current was observed for each prepared Fe(II)-based reducing agent.
[0188] Table 1. Oxidation potential
[0189]
[0190] Fig.16Polarization curves are shown for EDTA-LiOH solution and Fe(III)-EDTA in LiOH solution. It can be observed that the reduction peak of Fe(III)-EDTA in this medium appears at a potential less negative than that of the hydrogen evolution reaction, which confirms the possibility of electrochemically regenerating Fe(II)-EDTA from Fe(III)-EDTA at reasonable coulombic efficiency while minimizing the current associated with hydrogen formation.
[0191] Embodiment 7:
[0192] (a) Relithiation of FePO4 by Fe(II)-EDTA
[0193] To demonstrate the use of Fe(II)-EDTA for the relithiation of FePO4, 50 ml of a solution prepared according to a procedure similar to that described in Example 6 was contacted with 0.65 g of FePO4 prepared in Example 1(a) under an argon atmosphere at 40°C. For this assay, the EDTA concentration was increased to achieve an EDTA / Fe(II) molar ratio of 4, and the pH was adjusted to 8 with a 1 M LiOH solution to maximize the solubility of the redox couple. The FePO4 powder was kept suspended using a magnetic stirrer and the decrease in Fe(II)-EDTA concentration and the appearance of Fe(III)-EDTA were monitored using an ORP sensor placed in the suspension.
[0194] Fig.17 The potential change of the suspension during the relithiation process is shown. An increase in potential can be observed when Fe(II)-EDT is oxidized (by reducing FePO4 to LiFePO4) to Fe(III)-EDTA.
[0195] At the end of this assay, the solid was isolated by vacuum filtration, washed, dried and analyzed by X-ray diffraction (RigakuMiniFlex TM 600) analysis. Comparison of the graphs of pristine LiFePO4, delithiated FePO4 and the solid obtained after contact with Fe(II)-EDTA solution and in the presence of a lithium salt ( Fig.18 ) showed that the solid treated with Fe(II)-EDTA solution was completely relithiated to form LiFePO4.
[0196] (b) Relithiation of FePO4 by Fe(II)-citrate
[0197] Relithiation assays were performed using Fe(II)-citrate solutions similar to the procedure given for Fe(II)-EDTA in Section 7(a). In this example, the citrate / Fe(II) ratio was adjusted to 2 by the addition of ferrous sulfate and the pH was adjusted to 6 by the addition of 1 M LiOH. 50 ml of this solution was contacted with 0.19 g of FePO4 prepared in Example 1(a) under an argon atmosphere at 40°C. The FePO4 powder was kept in suspension using a magnetic stirrer and the decrease in Fe(II)-citrate concentration and the appearance of Fe(III)-citrate were monitored using an ORP sensor placed in the suspension ( Fig.19 ).
[0198] At the end of this test, the solid was isolated by vacuum filtration, washed, dried and analyzed by X-ray diffraction. As in the case of the solid of Example 7(a), comparison of the diffraction patterns of the original LiFePO4, the delithiated FePO4 and the solid obtained after contact with the Fe(II)-citrate solution and in the presence of a lithium salt ( Fig. 20 ) indicates that FePO4 is fully relithiated to form LiFePO4.
[0199] Embodiment 8:
[0200] (a) Electrochemical regeneration of Fe(III)-EDTA in Fe(II)-EDTA
[0201] A volume of 800 ml of Fe(III)-EDTA solution having initial Fe(III), Li2SO4 and EDTA concentrations of 0.08 M, 1 M and 0.2 M, respectively, and having its pH adjusted to 6.3 with LiOH, was placed in the cathode electrolyte reservoir of an ICI-FM01 filter press electrolyzer assembly and under the protection of an inert gas (Ar). The FM01 cell consists of a graphite cathode, a titanium anode coated with an iridium oxide layer and a Nafion TM The geometric effective surface area of all components (cathode, anode and membrane) is 64 cm 2 .
[0202] The cathode electrolyte and anolyte flow rates were 2 liters / minute, and the linear cathode electrolyte velocity was about 16 cm / s. The electrolysis temperature was controlled at about 50°C by circulating a heat transfer fluid heated by a thermostatic bath (PolyScience #PD07R-20-A11B) through heat exchangers installed in the anode electrolyte and cathode electrolyte tanks. Electrolysis was performed by setting the voltage between the anode and cathode to 1.65V (Instek #SPS-1230). An ORP sensor was placed in the cathode electrolyte reservoir to monitor the potential evolution of the solution.
[0203] The Fe(III)-EDTA concentration in each sample during electrolysis was determined by diluting 1 ml of sample in 10 ml of 0.2 M EDTA-LiOH solution (pH 7.70) and by measuring the absorbance of the solution at 470 nm. TM The total iron concentration was determined by adding the iron reagent and measuring the absorbance at 510 nm. The difference between total iron and Fe(III)-EDTA made it possible to estimate the concentration of Fe(II)-EDTA formed during the electrolysis. Fig.21 Shown are changes in the Fe(II)-EDTA concentration and redox potential of the solution during 240 minutes of electrolysis.
[0204] It can be observed that as the concentration of Fe(II)-EDTA (formed by reduction of Fe(III)-EDTA at the cathode) in the cathode electrolyte increases, the redox potential of the solution decreases. During the electrolysis, the total cell current decreases from 600 mA to 300 mA.
[0205] It should be noted that it is possible to increase the current density of the cell by improving the mass transfer in the cell by known methods (such as the use of turbulence promoters, increasing the temperature, etc.) and by increasing the effective surface area of the cathode (for example by using materials in the form of felt, grids, etc.). Obviously, the choice of cathode material is not limited to graphite, and other cathode materials (preferably those with a high hydrogen overpotential) can be used. (b) Relithiation of FePO4 with electrochemically generated Fe(II)-EDTA
[0206] The Fe(II)-EDTA solution obtained during the electrolysis with the FM01 cell in (a) was subsequently used for the relithiation of FePO4. 50 ml of this solution was contacted with 0.32 g of FePO4 prepared in Example 1(a) under an argon atmosphere at 40° C. The FePO4 powder was kept suspended using a magnetic stirrer and the decrease in the Fe(II)-EDTA concentration and the appearance of Fe(III)-EDTA were monitored using an ORP sensor placed in the suspension. Fig. 22 The potential change of the suspension during the relithiation process is shown. An increase in potential can be observed when Fe(II)-EDT is oxidized to Fe(III)-EDTA (by reducing FePO4 to LiFePO4).
[0207] At the end of this test, the solid was isolated by vacuum filtration, washed, dried and analyzed by X-ray diffraction. Comparison of the graphs of the original LiFePO4, the delithiated FePO4 and the solid obtained after contact with a Fe(II)-EDTA solution generated by electrolysis and in the presence of a lithium salt ( Fig.23) indicates that the solid is fully relithiated to form LiFePO4.
[0208] Many modifications may be made to any of the embodiments described above without departing from the scope of the invention as contemplated.Any reference, patent or scientific literature material mentioned in this application is hereby incorporated by reference in its entirety for all purposes.
Claims
1. A method for electrochemical alkalization of an electrochemically active material, the method comprising the steps of: a) obtaining a working electrode comprising a working electrode material on a current collector, the working electrode material comprising an electrochemically active material, optionally a binder and / or an electronically conductive material; b) introducing the working electrode into an electrochemical reactor with an inert counter electrode and a solution of an alkali metal salt contained in a solvent in a continuous and / or batch mode; c) applying a direct current between the working electrode and the counter electrode to obtain an alkalized electrode comprising an alkalized electrochemically active material; and d) removing the alkalized electrode obtained in step (c) from the electrochemical reactor; The method comprises the step of treating an electrochemically active material of formula I: A w-p M n+p x X y O z (I) Conversion into an alkalized electrochemically active material of formula II: HAS w M n x X y O z (II) in, A is an alkali metal; M is a transition metal, a post-transition metal or a combination thereof; X is selected from P, Si and S; O is an oxygen atom; w is selected from a value of 1 to 4 and corresponds to the number of A atoms in the alkalized electrochemically active material; x is selected from a value of 1 to 5 and corresponds to the number of M atoms; y is selected from a value of 0 to 2, wherein when y is 0, X is absent; z is selected from values 1 to 12 and corresponds to the number of oxygen atoms in the formula; n indicates the oxidation state of M; p in Formula I indicates the average number of missing A atoms and the average increase in the oxidation state of M, where p≤w; and wherein w, y, z, n and p are selected to provide a stable electrically neutral compound; and wherein the electrochemically active material is alkali metal deficient.
2. The method according to claim 1, wherein p is 0 <p≤1。 3. The method according to claim 1, wherein in formula I p=w, A is absent, and the electrochemically active material of formula I is of formula I(a): M n+p x X y O z .
4. The method according to claim 1, wherein X is phosphorus, y is 1, and z is 4.
5. The method according to claim 1, wherein M is Fe, Ni, Mn, Co or a combination of at least two thereof.
6. The method according to claim 1, wherein M is V, Mn, Ni, Co, Fe, Cr, Ti, Zr, Sn or a combination of at least two thereof.
7. The method according to claim 1, wherein y is 0 and X is absent.
8. The process according to any one of claims 1 to 7, wherein A is Li, Na or K.
9. The method according to claim 8, wherein A is Li.
10. The method according to any one of claims 1 to 7 or 9, wherein the electrochemically active material or alkalized electrochemically active material is further doped by partial substitution of M by transition metals and / or non-transition metals.
11. The method according to claim 10, wherein the transition metal is Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Mo, W or Y.
12. The method according to claim 10, wherein the non-transition metal is Mg, Ca, Sr, Al, Sb or Sn.
13. The method according to any one of claims 1 to 7 or 9, wherein the solvent is selected from an aqueous solvent, an organic solvent or a mixture thereof.
14. The method according to claim 13, wherein the solvent is water.
15. The method according to any one of claims 1 to 7 or 9, wherein the alkali metal salt comprises at least one alkali metal sulfate, carbonate, bicarbonate, hydroxide, nitrate, acetate, oxalate or phosphate.
16. The method according to claim 15, wherein the alkali metal salt is an alkali metal sulfate.
17. The method according to claim 15, wherein the alkali metal salt is an alkali metal bicarbonate.
18. The process according to claim 17, wherein steps (b) and / or (c) are carried out in the presence of gaseous carbon dioxide.
19. A method according to any one of claims 1 to 7 or 9, further comprising the step of adjusting the pH of the solution to a pH suitable for the electrochemically active material of step (a).
20. The method of claim 19, wherein the electrochemically active material of step (a) is FePO4 and the pH is adjusted to between 5 and 9.
21. The method according to claim 20, wherein the pH is adjusted to between 6 and 7.
5.
22. A process according to any one of claims 1 to 7, 9, 17 or 18 wherein the alkali metal of the alkali metal salt is lithium.
23. The method according to claim 15, wherein the alkali metal of the alkali metal salt is lithium.
24. The process according to any one of claims 1 to 7, 9, 17 or 18, wherein step (c) is carried out in a continuous mode or in a batch mode.
25. A method according to claim 24, wherein step (c) is carried out in a continuous mode, wherein the working electrode is introduced into the electrochemical reactor on one side and moved along a specified path so that the working electrode maintains a constant distance from the counter electrode while moving along the electrochemically active area of the electrochemical reactor to maintain a relatively uniform current and potential distribution.
26. The method of claim 25, wherein the speed at which the working electrode moves through the electrochemical reactor is adjusted based on the residence time required to achieve a desired level of alkalization at the applied current density.
27. A method according to any one of claims 1 to 7, 9, 17 or 18, wherein step (c) is carried out in a controlled current density mode between the working electrode and the counter electrode.
28. A method according to any one of claims 1 to 7, 9, 17 or 18, wherein step (c) is carried out in a controlled voltage mode between the working electrode and the counter electrode.
29. A method according to any one of claims 1 to 7, 9, 17 or 18, wherein the electrochemically active material is FePO4 or partially delithiated LiFePO4, and the current density at the working electrode is in the range of 0.001 A / g to 100 A / g active LiFePO4.
30. The method according to claim 29, wherein the current density at the working electrode is in the range of 1 to 15 A / g active LiFePO4.
31. A process according to any one of claims 1 to 7, 9, 17 or 18, wherein step (c) is carried out at a temperature of from 5°C to 90°C.
32. The process according to claim 31, wherein step (c) is carried out at a temperature of 25°C to 50°C.
33. A method according to any one of claims 1 to 7, 9, 17 or 18, wherein step (b) further comprises a reference electrode.
34. The method according to any one of claims 1 to 7, 9, 17 or 18, further comprising a step (e) of washing the alkalized electrochemically active electrode material of the alkalized electrode.
35. The method of any one of claims 1 to 7, 9, 17 or 18, further comprising drying the alkalized electrochemically active material of the alkalized electrode.
36. A method according to any one of claims 1 to 7, 9, 17 or 18, wherein the working electrode material comprises a binder selected from fluoropolymer binders and other solvating polymer binders.
37. The method according to claim 36, wherein the adhesive is a fluoropolymer adhesive.
38. The method according to claim 37, wherein the fluoropolymer binder is PVDF, HFP, PVDF-Co-HFP or PTFE.
39. A method according to claim 36, wherein the binder is a solvated polymer binder selected from the group consisting of poly(ethylene oxide), poly(propylene oxide), poly(dimethylsiloxane), poly(alkylene carbonates), poly(alkylene sulfones), poly(alkylene sulfonamides), polyurethanes, poly(vinyl alcohols), and copolymers comprising at least one of the foregoing polymers or monomers thereof, and combinations of at least two thereof, the polymers being optionally branched and / or cross-linked.
40. A method according to any one of claims 1 to 7, 9, 17 or 18, wherein the working electrode material comprises an electronically conductive material selected from carbon black, acetylene black, graphite, graphene, carbon fiber, carbon nanotubes, and a combination of at least two thereof.
41. The method according to claim 40, wherein the carbon fibers are carbon nanofibers.
42. A method according to any one of claims 1 to 7, 9, 17 or 18, wherein the working electrode material is an electrode material from a spent battery and step (a) comprises at least one step of separating the electrode material from other elements of the spent battery and applying the material to a current collector.
43. A method according to any one of claims 1 to 7, 9, 17 or 18, wherein step (a) comprises mixing the electrochemically active material, the binder and optionally the electronically conductive material in a solvent, applying to a current collector and drying.
Citation Information
Patent Citations
Phased introduction of lithium into the pre-lithiated anode of a lithium ion electrochemical cell
US20180040914A1
Process for the recycling of lithium battery electrode materials
US20190207275A1
Lithium ion battery with lithium vanadium pentoxide positive electrode
US5496663A
Reintroduction of lithium into recycled battery materials
US9287552B2
Systems and methods for preparing stabilized lithiated electrodes for electrochemical energy storage devices
WO2019070896A1